2017
DOI: 10.1002/cite.201700021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functionalization of Ordered Large‐Pore Mesoporous Silica Nanoparticles for Biomedical Applications

Abstract: A dual surfactant synthetic approach was employed for the synthesis of large-pore mesoporous silica nanoparticles (MSNs). The as-synthesized mesoporous silica exhibited not only 2D hexagonal mesostructure with an average pore size of about 7 nm but also a spherical nanoparticulate morphology. A delayed co-condensation synthesis method was further employed to create site-specific core-shell bifunctional MSNs. These core-shell large-pore MSNs are biocompatible and can be efficiently taken up by cells. They are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Such an approach was recently used to make mesoporous silica nano-size particles of silica with large pores. [35] These materials had both two dimensional hexagonal mesostructures that have pore sizes of roughly 7 nm as well as nano-particulates having a spherical morphology. The authors used a synthetic method involving delayed co-condensation in order to make bifunctional coreshell nano-sized mesoporous silicas that are site specific.…”
Section: Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach was recently used to make mesoporous silica nano-size particles of silica with large pores. [35] These materials had both two dimensional hexagonal mesostructures that have pore sizes of roughly 7 nm as well as nano-particulates having a spherical morphology. The authors used a synthetic method involving delayed co-condensation in order to make bifunctional coreshell nano-sized mesoporous silicas that are site specific.…”
Section: Future Studiesmentioning
confidence: 99%
“…As such these materials are carriers of nano-size mesoporous materials that can be used to deliver different species to cells. [35] Combinations of methods will also likely happen as will miniaturization of some instrumentation. These combinations may be important in characterization studies as well as in syntheses or in catalytic reactions.…”
Section: Future Studiesmentioning
confidence: 99%
“…There are many methods to realize CMSN with large mesopores, including prolonging the length of the template agent chain, changing templates, adjusting pH of the synthesized system and adding additives. For instance, the mesopores can be enlarged to 10 nm using designed surfactant [10,11,12]. It was reported that mesopores in the range of 3.8 to 20 nm can be regulated by controlling systemic pH.…”
Section: Introductionmentioning
confidence: 99%
“…MSP are chemically synthesized either in the form of ordered or unordered particles varying in their internal arrangement involving the pores and structures [16,17]. Several ingredients though engaged in the synthesis, main components of MSP system consists of a silica precursor and structure directing surfactants.…”
Section: Introductionmentioning
confidence: 99%